PTH-128 Low fodmaps diet in ibs is more effective for constipation than other symptoms in joint hyperombiolty syndrome. (17th June 2017) - Fragkos, KC; Cox, A; Barragry, J; Eady, J; Keetarut, K; Zarate-Lopez, N; Emmanuel, A
Abstract : Introduction: A low FODMAPs diet is now an established strategy for the management of irritable bowel syndrome (IBS). Patients with joint hypermobility syndrome (JHS), a non-inflammatory connective tissue disorder, frequently report functional gut symptoms, often fulfilling criteria for IBS. A low FODMAPs diet effect is known to reduce bowel distension and gas generation secondary to modified food fermentation, impacting on visceral hypersensitivity, and hence potentially improving pain in IBS. Method: Consecutive patients fulfilling the Rome III criteria for IBS referred to a dedicated dietician clinic for implementation of the low FODMAP diet were included in the study. Patients who completed low FODMAPs dietary education therapy were analysed. Symptoms were assessed at baseline and follow up (median 63 days post-treatment) via self-administered questionnaire. The primary endpoint was a symptom severity score (scale 0–5) based on pain, bloating, constipation and diarrhoea. Patients with a positive diagnosis of JHS made by an experienced rheumatologist were identified. Results: 170 patients (135 F, age 43±14 years) were included in the analysis of whom 35 (34 F) had JHS. This female preponderance of comorbid JHS and IBS was statistically significant (p=0.003). A disproportionately larger proportion of patients with both JHS and IBS had constipation-predominant IBS than other subtypes (p<0.05). Baseline IBS symptom severity was similar between both groups before intervention (p=0.06) except for pain which was significantly higher in patients with JHS (3.8 vs 3.23, p=0.01). Across all patients, an improvement in symptom severity (2.4 to 1.6, p<0.001) was observed following low FODMAPs diet (see figure). A repeated measures mixed model with JHS variable, IBS type and dietetic intervention revealed that pain was significantly reduced in patients with JHS after dietetic intervention (p<0.0001). In IBS-C and IBS-mixed, constipation severity only improved significantly in hypermobile patients (p<0.05). Conclusion: In this cohort, there is a difference in IBS subtypes between patients with and without JHS, with IBS-C being especially prevalent in JHS patients. A low FODMAPs diet is effective in improving symptoms in patients with IBS and JHS. In particular, pain and constipation are especially improved in patients with JHS. Disclosure of Interest: None Declared